MODEL PENINGKATAN KINERJA SDM BERBASIS PERSON JOB FIT DAN MOTIVASI BERPRESTASI - Jujuk Juhroliyah (Jurnal Riset Bisnis Indonesia, 2016)
The purpose of this research is to test the influences of person job fit, and achievement motivation,on professional competence to increase SDM performance moderated by work monitoring. Usingthese variables, the usage of these variables are able to solve the arising problem within employeesresidences of Kabupaten Semarang. Statement of this problem is how increase SDM performance?.The samples size of this research is 105 employees residences of Kabupaten Semarang. Using theStatistical Package Social Science (SPSS). The results show that person job fit, and achievementmotivation, on professional competence to increase SDM performance moderated by work monitoring.The effect of person job fit on achievement motivation are significant; The effect of person job fiton professional competence are significant; The effect of achievement motivation on professionalcompetence are significant; work monitoring moderating influence professional competence on SDMperformance are significant..Keywords: person job fit, achievement motivation, professional competence and SDMperformance.